A single compound alternative to A Buprenorphine/Naltrexone combination to prevent relapse to drug addiction - Ridzwan, Irna Elina; Clarke, Mary; Traynor, J.; Husbands, Stephen M; Bailey, Christopher P (Wiley-Blackwell, 2012)
Recent studies suggest the combination of buprenorphine and naltrexone is a promising drug lead to prevent relapse to drug taking [1]. However it has proven to be a challenge to design a single formulation of this combination due to different routes of administration needed in the clinical setting. In this project, we targeted buprenorphine analogues as single compound mimics of the combination, having lower efficacy at mu opioid receptors (MOR) than buprenorphine, but retaining buprenorphine's activity at kappa (KOR) and ORL-1 receptors.